Optimal strategies for transitions in simulated moving bed chromatography. (4th January 2016) - Vignesh, S.V.; Hariprasad, K.; Athawale, Pratik; Siram, Vinod; Bhartiya, Sharad
Abstract : Highlights: Optimal strategies for transitions between operational modes of SMBC is proposed. Approach resulted in significant savings in time, feed and desorbent consumption. Also addresses optimal recovery from unanticipated feed grade changes. Optimal transition policies consistent with equilibrium triangle theory for SMBC. Abstract: Simulated moving bed chromatography (SMBC) has emerged as a significant separation technology in the process industry. SMB operating parameters are chosen to satisfy various performance objectives such as maximization of purity or productivity and the choice of the objective is generally guided by process economics. From an industrial perspective, the SMB must be operated flexibly, so that the same unit can be operated to satisfy different objectives. Transiting from one objective to another entails large transition periods, resulting in an economic loss. We propose use of optimal transitions as an approach to minimizing transition time, reducing use of feed and desorbent during transition as well as reduction in off-specification product relative to a non-optimal, step change approach. Optimal transitions can also be used in recovering from feed upset scenarios. The above methods are demonstrated using simulations on a benchmark SMBC process for separation of glucose and fructose using Ca ++ exchange resin.